M51 ULX-7: when strong beaming is not needed to explain super-Eddington luminosities - Vasilopoulos, G.; Haberl, F.; Brightman, M.; Earnshaw, H.; Treiber, H.; Koliopanos, F. (2021)
M51 ULX-7 is a an ultraluminous X-ray pulsar (ULXP) with a spin period of ~2.8 s, and orbital period of ~2 d, and a maximum luminosity that exceeds by more than 20 times the Eddington limit for a neutron star (NS). An open question about ULXPs, is if indeed the mass accretion rates are super-Eddington, or the emission is beamed due to the presence of strong optically thick outflows. Such outflows could originate from the disk and may form a narrow funnel allowing radiation to escape only towards the observer. We will discuss the temporal properties of the system based on the analysis of archival X-ray data collected by Swift/XRT and Chandra. We find that its X-ray flux modulates with a super-orbital period of ~40 d, while there appear to be epochs where the pulsar transitions to the propeller stage. Moreover, we report the discovery of periodic X-ray dips, with a period that matches the orbital period. The observable properties of M51 ULX-7 can be used to probe the mass accretion rate onto the NS and to constrain the orbital inclination of the binary. We conclude that the properties of the systems are evident of a small beaming factor and a wide funnel, thus demonstrating that strong beaming does not need to be invoked to explain the observed fluxes, and that super-Eddington accretion rates are possible for highly magnetized NSs.